Deposition of refractory metal films with planar plasma ECR source - Fedorchenko, V.D.; Chebotarev, V.V.; Medvedev, A.V.; Tereshin, V.I. (Вопросы атомной науки и техники, 2007)
The condition of the deposition of refractory metal and alloy films such as W, Mo, Ti, Ta, Cr, Ni, Fe₈₀B₂₀ with using ECR plasma source at the different magnitudes of bias voltage on targets and substrates were investigated. It was revealed that the maximal rate of the films growth amounted to 0,052 µm/min for Cr. The thicknesses of the films were obtained of 16-20 µm in the current experiments. Досліджено умови нанесення покритій тугоплавких металів, таких як W, Mo, Ti, Ta, Cr, Ni, а також сплава Fe₈₀B₂₀ з використанням ЕЦР плазмового джерела при різних величинах напруги на мішені та підкладці. Показано, що максимальна швидкість росту товщини покриття складала 0,052 мкм/хв для Cr. В даних експериментах були отримані покриття товщиною порядку 16 - 20 мкм. Исследованы условия нанесения покрытий тугоплавких материалов, таких как W, Mo, Ti, Ta, Cr, Ni, а также сплава Fe₈₀B₂₀ с использованием ЭЦР плазменного источника при различных величинах смещения напряжения на мишени и подложке. Показано, что максимальная скорость роста толщины покрытия составляла 0,052 мкм/мин для Cr. В данных экспериментах были получены покрытия толщиной порядка 16 - 20 мкм.